2021
DOI: 10.1101/2021.10.16.464660
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Boosting of SARS-CoV-2 immunity in nonhuman primates using an oral rhabdoviral vaccine

Abstract: An orally active vaccine capable of boosting SARS-CoV-2 immune responses in previously infected or vaccinated individuals would help efforts to achieve and sustain herd immunity. Unlike mRNA-loaded lipid nanoparticles and recombinant replication-defective adenoviruses, replicating vesicular stomatitis viruses with SARS-CoV-2 spike glycoproteins (VSV-SARS2) were poorly immunogenic after intramuscular administration in clinical trials. Here, by G protein trans-complementation, we generated VSV-SARS2(+G) virions … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…76,78,79 Notably, IN/ OM vaccination was highly immunogenic and induced serum nAbs in all animals in this study (Figure 5b and c), whereas a single dose delivered by just the OM route was immunogenic but not consistently (two of five OM-vaccinated animals responded), which may be similar to the lack of immunogenicity seen in macaques after a single oral dose. 94 Together these results indicated that the application of VSVΔG-SARS-CoV-2 to the mucosal epithelium in the nasal cavity, nasopharynx, and possibly the lower respiratory tract was the main contributor to the strong immunogenicity seen with the IN/OM vaccination method. A follow-up hamster study (Figure 7) was then conducted using a small volume of VSVΔG-SARS-CoV-2 #9 applied only to the nasal cavity to restrict most of the vaccine inoculum to the nasal epithelium.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…76,78,79 Notably, IN/ OM vaccination was highly immunogenic and induced serum nAbs in all animals in this study (Figure 5b and c), whereas a single dose delivered by just the OM route was immunogenic but not consistently (two of five OM-vaccinated animals responded), which may be similar to the lack of immunogenicity seen in macaques after a single oral dose. 94 Together these results indicated that the application of VSVΔG-SARS-CoV-2 to the mucosal epithelium in the nasal cavity, nasopharynx, and possibly the lower respiratory tract was the main contributor to the strong immunogenicity seen with the IN/OM vaccination method. A follow-up hamster study (Figure 7) was then conducted using a small volume of VSVΔG-SARS-CoV-2 #9 applied only to the nasal cavity to restrict most of the vaccine inoculum to the nasal epithelium.…”
Section: Discussionmentioning
confidence: 82%
“…The hypothesis that skeletal muscle is not an effective site for Spike-dependent VSVΔG-SARS-CoV-2 replication also has been discussed by others based on their research with similar chimeric viruses. 50,86,94 Thus, although the VSVΔG-SARS-CoV-2 particles displaying Spike arrays might be quite immunogenic after IM injection in rodents in the absence of significant infection and replication, it is conceivable that a similar quantity of virion particles injected a single time into a much larger macaque 94 or human muscle 18 would be less immunostimulatory in the absence of a potent adjuvant, administration of a booster dose, 95 or immune system priming, for example, by previous infection with SARS-CoV-2. 18 Our investigation of differing routes of vaccine administration (Figures 3 and 5) suggests that mucosal vaccination results in a greater immune response to VSVΔG-SARS-CoV-2 in hamsters compared with IM injection and that IN vaccination may be optimal (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were incubated at 37°C in 5% CO2 with saturating humidity. The Indiana strain-based VSV expressing SARS-CoV-2 spike in place of VSV-G and trans-complemented with VSV-G has been described elsewhere 66 . The recombinant measles virus (rMeV) based on the Moraten vaccine strain expressing firefly luciferase has been described previously 46 .…”
Section: Cells and Virusesmentioning
confidence: 99%